Modification of the content of n-3 highly unsaturated fatty acid, chemical composition, and lipid nutritional indices in the meat of grass carp (Ctenopharyngodon idella) fed alfalfa (Medicago sativa) pellets - Montenegro, Luciano Federico (2020)
A 120-d feeding trial was conducted to determine the effect of alfalfa (Medicago sativa) feeding on growth and chemical composition, fatty acid content, and nutritional and lipid indices of the meat of grass carp (Ctenopharyngodon idella). Two experimental diets were used: alfalfa pellet (AP) diet and artificial grain diet (GD). Final weight, feed conversion rate, and protein efficiency ratio were significantly greater in the GD group (P < 0.05). However, no differences in the length and condition factor were observed. The composition of the meat differed between treatments. The protein content was significantly greater in the AP group (P < 0.05), while the lipid and cholesterol contents were significantly greater in the GD group (P < 0.05). A greater proportion of saturated, n-6 polyunsaturated, and n-6 highly unsaturated fatty acids was obtained in the GD group. The AP group accumulated a greater concentration of eicosapentaenoic (EPA), docosapentaenoic (DPA), and docosahexaenoic (DHA) acids (P < 0.05). The fatty acid composition of the meat determined a significant decrease in the thrombogenicity index and saturation index (S/P) in the AP group (P < 0.05). The Elongase index was greater in the GD group (P < 0.05). In contrast, the AP group had a greater index of Δ9 Desaturase and Δ5 + Δ6 Desaturase for n-3 and n-6 fatty acids (P < 0.05). These results suggest that alfalfa feeding decreases the growth of C. idella but improves the quality of meat by increasing the protein, EPA, and DHA contents. It also reduces cholesterol content and improves nutritional indices.